Incorporating credit quality in bank efficiency measurements: A directional distance function approach - Abdul Qayyum Khan; Khalid Riaz (Journal of Risk and Financial Management, 2018)
The objective of the study was to measure the risk-adjusted efficiency of banks in 24 emerging economies for the period of 1999-2013. A two-stage network data envelopment analysis (DEA), with separate deposit mobilization and loan financing stages was used. Efficiency was measured using directional distance functions with DEA, featuring non-performing loans as undesirable outputs. The distributions of efficiency scores were different when credit quality was taken into account. The distribution of efficiency scores varied systematically with accumulation of non-performing loans across regions. The financial crisis of 2007-2008 impacted more adversely the regions that had higher proportions of non-performing loans in banks' portfolios. The results of a follow-on non-parametric regression showed that smaller, better capitalized, and private banks were more efficient. The conditions conducive for high levels of technical efficiency by banks were found to be characterized by economic growth and low inflation.
Keywords: 330; emerging economies; banks; directional distance functions; network DEA; non-parametric regression